PENGARUH CITRA MEREK, HARGA PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MIXUE DI YOGYAKARTA - Nunuk D. G. Endang Palupi; Diana Leli Indratno; Rinaldi Rinaldi; Azwar Azwar; Lalu Supardin (ITB AAS Indonesia Surakarta, 2023)
This study aims to determine and analyze the effect of brand image, product price, and product quality on purchase decision Mixue in Yogyakarta. The data collection method was carried out by distributing questionnaires to research respondents. The sample used in this study were respondents who had purchased Mixue products in Yogyakarta. The number of samples used in this study were 100 respondents. This study uses multiple linear regression analysis as a data analysis method using SPSS 24 software. The findings in this study are divided into four findings: first, brand image has a significant effect on purchase decisions Mixue in Yogyakarta. Second, product price has no significant effect on purchase decisions Mixue in Yogyakarta. Third, product quality has a significant effect on purchase decisions Mixue in Yogyakarta. Fourth, brand image, product price and product quality on purchase decisions Mixue in Yogyakarta Keywords: Brand Image, Product Price, Product Quality, Purchase Decision